Antecedents of Business Tourist Loyalty: The Moderating Role of Familiarity and Emotional and Cognitive Experiences - Marinao-Artigas, E (Springer Science and Business Media Deutschland GmbH, 2025)
This study verifies whether some environmental components of business destinations and inherent to the behavior of business tourists and act in a dyadic way as drivers of business tourist loyalty. Furthermore, it aims to test whether business tourists’ familiarity and emotional and cognitive experiences played a moderating role. This objective is to be achieved using quantitative and experimental methodological designs. A structural equation model is used to validate the hypotheses in this study. A questionnaire consisting of 76 questions is administered to a non-probabilistic sample of foreign business executives who visited Mexico City in Mexico and Santiago de Chile. The results of this study prove that the dyadic path formed by perceived quality, reputation, trust, and satisfaction becomes the best synergistic support for business tourist loyalty. Moreover, familiarity with a business destination and the emotional and cognitive experiences of the business tourist strengthen perceived quality, reputation, trust, and satisfaction paths. The originality of this study lies in confirming, in an unprecedented way, a sequence of environmental components and inherent to business tourists’ behavior as drivers of their loyalty to the business destination. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2025.